Stability of molybdenum nanoparticles in Sn-3.8Ag-0.7Cu solder during multiple reflow and their influence on interfacial intermetallic compounds - Haseeb, A.S. Md. Abdul; Arafat, M.M.; Johan, M.R. (2012)
This work investigates the effects of molybdenum nanoparticles on the growth of interfacial intermetallic compound between Sn-3.8Ag-0.7Cu solder and copper substrate during multiple reflow. Molybdenum nanoparticles were mixed with Sn-3.8Ag-0.7Cu solder paste by manual mixing. Solder samples were reflowed on a copper substrate in a 250 degrees C reflow oven up to six times. The molybdenum content of the bulk solder was determined by inductive coupled plasma-optical emission spectrometry. It is found that upon the addition of molybdenum nanoparticles to Sn-3.8Ag-0.7Cu solder, the interfacial intermetallic compound thickness and scallop diameter decreases under all reflow conditions. Molybdenum nanoparticles do not appear to dissolve or react with the solder. They tend to adsorb preferentially at the interface between solder and the intermetallic compound scallops. It is suggested that molybdenum nanoparticles impart their influence on the interfacial intermetallic compound as discrete particles. The intact, discrete nanoparticles, by absorbing preferentially at the interface, hinder the diffusion flux of the substrate and thereby suppress the intermetallic compound growth. (C) 2011 Elsevier Inc. All rights reserved.